Kesultanan Melayu Kedah - Rogayah A. Hamid , 1954-; Mariyam Salim , 1953- (Siri kajian naskhah kesultanan Melayu, 2006)
History of Malay sultanates in the Malay manuscript and literature; volume commemorating the 50th anniversary of Dewan Bahasa dan Pustaka